2011
DOI: 10.1089/cmb.2011.0031
|View full text |Cite
|
Sign up to set email alerts
|

Boolean Models Can Explain Bistability in the lac Operon

Abstract: The lac operon in Escherichia coli has been studied extensively and is one of the earliest gene systems found to undergo both positive and negative control. The lac operon is known to exhibit bistability, in the sense that the operon is either induced or uninduced. Many dynamical models have been proposed to capture this phenomenon. While most are based on complex mathematical formulations, it has been suggested that for other gene systems network topology is sufficient to produce the desired dynamical behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(120 citation statements)
references
References 21 publications
3
116
0
Order By: Relevance
“…Details of the ODEs and rate equations are given in the supplementary material. The model of the lac operon was based upon [8,9] and [11]. The model of MAP kinase signalling is based upon that of Brightman and Fell [21], and the model of PI3K signalling was adapted from [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the ODEs and rate equations are given in the supplementary material. The model of the lac operon was based upon [8,9] and [11]. The model of MAP kinase signalling is based upon that of Brightman and Fell [21], and the model of PI3K signalling was adapted from [22].…”
Section: Methodsmentioning
confidence: 99%
“…Veliz-Cuba and Stigler [9] showed that Boolean models could explain bistability (i.e. the existence of stable ON or OFF states, but not intermediate states) in the lac operon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Francis Robert [10] defines 1 * 1 = 0, whereas other authors (for example [18]) consider 1 * 1 to be 1. Except of adding and multiplying variables, we are also allowed to add 1, which is equivalent to negation.…”
Section: Preliminaries a Boolean Functions And Dynamical Systemsmentioning
confidence: 99%
“…Large networks are hard to analyze mathematically, both from discrete and from continuous point of view [15], [17]. Usually in such cases a model reduction technique is applied [13], [17], [18], [19]. The authors of [1] base their model reduction strategy intended for CCNs on cell coloring.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation